Isolation and laboratory diagnosis of Capripoxvirus from goats in Shanxi Province - SHI Zhong-yong; SHI Xin-tao; YUAN Jian-qin; GU Shao-peng; CHEN Zhang-hui; ZHENG Mingxue (浙江大学学报. 农业与生命科学版)
For clinical diagnosis, the Capripoxvirus from crust materials of goats with clinical sore mouth symptom from a farm in Shanxi Province was isolated. Cytopathic effect (CPE) was observed in the third passage by transfecting the virus into lamb testis (LT) cells. Eosinophilic intracytoplasmic inclusions were detected in the cell culture by the hematoxylin-eosin (HE) staining. The animal showed a pox virus-infected symptom in the recurrent infection test and the result of enzyme-linked immunosorbent assay (ELISA) showed that the concentration of the virus in the sample was 6.835 IU·L-1, indicating the Capripoxvirus antigen was existed. It is indicated that the Capripoxvirus is separated and diagnosed successfully, and the results may be used for future research.